Cell wall acidification in growing barley (Hordeum vulgare L.) leaves - Visnovitz, Tamás (Acta Biologica Szegediensis, 2011)
Apoplast acidification associated with growth is well-documented in roots and coleoptiles but not in leaves. In the present study, advantage was taken of high cuticle permeability in the elongation zone of barley leaves to measure apoplast pH and acidification and the role which the plasma membrane H+ ATPase (PM-ATPase) plays in this process. An in-vitro gel system and pH-microelectrodes were used to monitor pH, and growth was measured with a linear variable differential transformer (LVDT). Test reagents which blocked (vanadate) or stimulated (fusicoccin) PM-ATPase were applied to the leaf elongation zone. In addition, the expression level (qPCR) and activity of PM-ATPase was determined. Apoplast pH was lower in growing compared with non-growing tissue. Growth and apoplast acidification were stimulated by fusicoccin and reduced by vanadate. Expression of PM-ATPase, as judged from Ct-values, was almost identical in the two leaf regions. In contrast, activity of PM-ATPase, expressed per unit plasma membrane protein, was about twice as high in growing tissue. It is concluded that PM-ATPase is required in growing leaf cells to achieve maximum rates of elongation and apoplast acidification and that this is due in part to a higher plasma membrane surface density of PM-ATPase activity.